On facies belts and facies mosaics: Holocene isolated platforms, South China Sea. Issue 7 (17th October 2016) - Rankey, Eugene C.
Abstract: Although the general criteria for recognition and environmental interpretation of different carbonate facies are well‐established, a predictive understanding of the areal extent and spatial patterning of facies bodies and why they might organize into facies belts or facies mosaics is poorly constrained. To explore patterns and process dynamics of facies on isolated carbonate platforms, quantitative analysis of thematic maps derived from remote sensing images of 27 Holocene atolls of the Paracel and Spratly chains in the South China Sea explores variability within and among platforms. On these systems, most annular shelf‐margin reefs are less than 500 m wide on both chains; inboard of the reefs, reef sand aprons range up to 500 m (Spratlys) and 1000 m (Paracels) wide. Around individual platforms, Spratly Chain sand apron widths are wider to the north‐west, whereas apron widths in the Paracel Chain are more symmetrical; collectively, data indicate log‐normal width‐exceedance probability distributions. Platform‐interior patch reefs include area‐exceedance probability distributions and gap size distributions (lacunarity) consistent within chains, but distinct between the chains. To understand the processes underlying distinct distributions, simulations explored distinct growth scenarios. Results suggest that differences may represent distinct process classes: proportional growth processes with multiplicative random effects (reef sand aprons – belts), versus non‐linear, size‐proportional growth of randomly aged and distributed elements (patch reefs – mosaics). The probabilistically distinct sizes and spatial patterns of geomorphic elements within these general process classes are interpreted to represent 'variations on themes' related to the different impacts of tropical storms, winter cold fronts and circulation in each chain. The results highlight fundamentally different growth patterns impacting the sizes and distribution of facies belts and mosaics on isolated carbonate platforms. Because these types of bodies ultimately construct stratigraphy, the themes could be applied to understand and predict variability in the architecture of subsurface reservoir analogues.